The Role of Centralization, Lean Operation, Risk Management Enhancement, and TB Organization Structure Implementation in Corporate Banking Operational Efficiency - Muhammad Zubayr (Journal of Applied Business Administration, 2025)
This study investigates the synergistic effects of operational centralization, risk management enhancement, and the Transaction Banking (TB) organization model in improving banking operational efficiency through lean operation principles at the SENTINEL Bank Jakarta Branch. Root cause analyses, including 5 Whys, Fishbone, and Pareto methods, identified key inefficiencies such as decentralization, unclear roles, lack of risk awareness, and fragmented governance. A mixed-methods approach was employed, combining Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis of employee surveys (n = 200) with workload benchmarking of transactional and Full-Time Equivalent (FTE) data. The findings reveal that operational centralization significantly enhances operational efficiency (STDEV = 0.066, T = 7.056, p = 0.000) by reducing non-value-added activities, standardizing workflows, and enabling over 70% cost savings. Lean operation principles also demonstrated a significant positive impact (STDEV = 0.249, T = 3.539, p = 0.000), with centralization and TB reorganization further strengthening lean practices. However, risk management enhancements, while positive, had no significant direct effect on operational efficiency (STDEV = 0.069, T = 0.827, p = 0.408), suggesting a more supportive rather than primary role. Similarly, the TB organizational structure’s direct impact on efficiency was statistically insignificant (STDEV = 0.240, T = 1.834, p = 0.067), indicating that structural changes must be accompanied by process optimization to realize full efficiency gains. This study contributes to the discourse on corporate banking efficiency by quantifying the interdependencies among structural reforms, lean operations, and risk management practices in addressing operational inefficiencies.